Pendampingan Lukis Wastra Tamarind di Atas Tote Bag untuk Mahasiswa Internasional di Loughborough, Inggris - Ariesa Pandanwangi; Cama Juli Rianingrum; Yudi Ariadi (Universitas Muhammadiyah Malang, 2026)
Purpose – Participants can improve their skills in creating wastra paintings on tote bags using sustainable tamarind materials. Design/methodology/approach – The service method is Asset-Based Community Development (ABCD). There were 42 participants who took part in this training from various countries. They come from Loughborough University in England. This activity need six stages from preparation starts in June 2025 to implementation on October 29, 2025. The location in the open area on the 2nd floor of the School of Design and Creative Arts building. Findings – As a result of these social services, participants improved their practical skills, as evidenced by the fact that as many as 42 works of painting were created on tote bags. The visual forms created mostly contain floral objects, basic geometric shapes, and everyday objects. The colors that appear are the colors resulting from the mixture, so that the colors on the visual object are very attractive, from light colors to gradations towards darker colors. This is because their background is from a part of the textile sector. Originality/value – The originality of this social service is that international community service can be a bridge for cultural diplomacy. The important point of this service is that Indonesia attention to sustainable environmental issues.